"n Semiotiese ontleding van Daniël 1 - Nel, Marius (HTS teologiese studies, 2006)
A Semiotic analysis of Daniel 1In this article the method of semiotic analysis is used in interpreting Daniel 1. At first, a short summary is given of the procedure before it is applied in a discussion of Daniel 1. Semiotics allows the researcher to analyze the functions and qualifications in the narrative in order to define pertinent transformations. In the process the role-players and plot are analyzed, leading to presentation of semiotic squares and the way the writer transfers values and convictions. The narrative programs are described, and the themes and characters identified. The important themes are the sovereignty of Israel’s God and responsibility of believers.